Collateral damage: The harm done to Swiss commercial interests by EU policies since the crisis began - Simon J. Evenett (Aussenwirtschaft, 2016)
Since the onset of the global economic crisis, on no occasion have the European Commission or European Union member state governments singled out Swiss commercial interests for discriminatory treatment. Even so, 200 official acts taken across the EU since November 2008 have caused collateral damage to Swiss commercial interests, three-quarters of which are still in force. Swiss exports worth more than 17 billion francs face one or more crisis-era trade distortion. However, inferred trade cost data reveal that Swiss commercial interests have been discriminated against more than other major suppliers to EU markets in only three member states.
Keywords: F02; F53; 330; Switzerland; European Union; free trade agreement; trade distortions; global economic crisis